The effects of different cooking methods on some fatty acid composition in sea bass grown in marine, freshwater, and culture environments - Ali Şen; Gürkan Uçar (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aimed to investigate the changes in fatty acid composition of sea bass fish grown in different environments (wild-freshwater environment, wild-marine environment, culture) as a result of applying three different cooking methods (deep fat frying, grilling, baking). Materials and Methods: 3 different cooking methods (deep fat frying, grilling, baking) were applied to sea bass fish grown in different environments (wild freshwater environment, wild marine environment, culture). 4 different groups were formed, including raw fish samples. The procedures applied in this research were carried out in triplicate. After the fish were washed and cleaned, they were made into fillets. Samples are adjusted to a minimum of 500 g. Fatty acid composition analysis was performed using the COI / T.20 / Doc.no.17 gas chromatographic method and GC-FID device. Results: he % fatty acids values obtained as a result of the analysis were determined as follows in the "freshwater, marine, culture" sea bass fish and in the "raw, deep fat frying, grilling, baking" cooking groups, respectively. Omega-3; (14.78; 9.19; 13.60; 9.89), (16.41; 9.35; 15.66; 10.34), (11.76; 9.73; 11.23; 9 ,41), omega-6; (18.52; 46.58, 12.36; 29.83), (22.53; 30.49; 12.86; 29.81), (18.19; 30.18; 18.30; 30 .34), saturated fat; (0.47; 0.51; 0.80; 0.38), (0.50; 0.58; 0.77; 0.50), (1.68; 1.21; 1.18; 2 .03), monounsaturated fat; (0.93; 1.29; 0.62; 0.97), (0.79; 1.35; 0.60; 1.16), (3.22; 2.73; 2.32; 4 .59), polyunsaturated fat; (0.70; 2.33; 0.51; 0.99), (0.93; 1.41; 0.56; 1.23), (2.45; 2.91; 1.72; 4 .83), ALA; (0.33; 1.31; 0.25; 0.63), (0.38; 0.27; 0.24; 0.57), (0.42; 0.42; 0.35; 0 ,28), EPA; (0.02; 0.01; 0.23; 0.02), (0.03; 0.01; 0.25; 0.03), (0.01; 0.01; 0.02; 0 .01), DHA; (5.72; 4.91; 10.64; 4.80), (8.26; 4.68; 12.36; 5.28), (5.47; 4.70; 5.18; 4 ,66). Conclusion: According to all fish groups and cooking methods, grilled wild sea bass is the most suitable in terms of omega-3. Freshwater sea bass cooked in deep fat fried is more suitable in terms of omega-6, baked cultured sea bass is more suitable in terms of mono and polyunsaturated fats, grilled wild marine sea bass is more suitable in terms of EPA and DHA. For deep fat frying methods is generally cultured fish more suitable, wild freshwater and marine fish are more suitable for oven cooking for diets low in saturated fat. When raw and cooked fish groups are compared, cooking processes have a significant effect on the approximate fatty acid composition of fish.